MOTIVATIONAL PATHWAYS TO EMPLOYEE PERFORMANCE IN VILLAGE CREDIT INSTITUTIONS - Komang Dewi Puspita; I Made Artha Wibawa (Adisam Publisher, 2026)
Employee performance is essential to the sustainability of Village Credit Institutions (LPDs), where service quality and financial accountability depend on employees' ability to perform effectively. This study examines the mediating role of work motivation in the relationships between the non-physical work environment, organizational culture, and employee performance. Questionnaire responses were obtained from 234 employees selected through proportionate random sampling across 35 Village Credit Institutions in Denpasar City, Indonesia. The proposed relationships were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS version 4.1. The findings confirm that the non-physical work environment and organizational culture positively influence both work motivation and employee performance. Work motivation also enhances employee performance and functions as a complementary partial mediator in the relationships between the non-physical work environment, organizational culture, and employee performance. The findings extend the application of Social Exchange Theory to community-based financial institutions by highlighting the importance of motivational processes in strengthening employee performance. Practically, the study suggests that improving interpersonal workplace relationships, organizational values, and employee motivation can support sustainable organizational performance in Village Credit Institutions.